Reduced striato‐cortical and inhibitory transcallosal connectivity in the motor circuit of Huntington's disease patients. Issue 1 (8th October 2017) - Garcia‐Gorro, Clara; de Diego‐Balaguer, Ruth; Martínez‐Horta, Saul; Pérez‐Pérez, Jesus; Kulisevsky, Jaime; Rodríguez‐Dechicha, Nadia; Vaquer, Irene; Subira, Susana; Calopa, Matilde; Muñoz, Esteban; Santacruz, Pilar; Ruiz‐Idiago, Jesús; et al.
Abstract: Huntington's disease (HD) is a neurodegenerative disorder which is primarily associated with striatal degeneration. However, the alterations in connectivity of this structure in HD have been underinvestigated. In this study, we analyzed the functional and structural connectivity of the left putamen, while participants performed a finger‐tapping task. Using fMRI and DW‐MRI, 30 HD gene expansion carriers (HDGEC) and 29 healthy participants were scanned. Psychophysiological interaction analysis and DTI‐based tractography were employed to examine functional and structural connectivity, respectively. Manifest HDGEC exhibited a reduced functional connectivity of the left putamen with the left and the right primary sensorimotor areas (SM1). Based on this result, the inhibitory functional connectivity between the left SM1 and the right SM1 was explored, appearing to be also decreased. In addition, the tract connecting these areas (motor corpus callosum), and the tract connecting the left putamen with the left SM1 appeared disrupted in HDGEC compared to controls. Significant correlations were found between measures of functional and structural connectivity of the motor corpus callosum, showing a coupling of both types of alterations in this tract. The observed reduction of functional and structural connectivity was associated with worse motor scores, which highlights the clinical relevance of these results. Hum Brain Mapp 39:54–71, 2018 . ©2017 Wiley Periodicals, Inc.